2015
DOI: 10.4314/ijbcs.v9i1.41
|View full text |Cite
|
Sign up to set email alerts
|

Etude des propriétés d’adsorption et de désorption du Plomb (Pb) et du Cadmium (Cd) par les sédiments d’une lagune tropicale en présence d’Allylthiourée

Abstract: RESUMELes métaux plomb (Pb) et cadmium (Cd) s'accumulent dans les réseaux trophiques aquatiques et peuvent présenter une menace pour la santé humaine et la faune. Une littérature relativement abondante existe sur la concentration totale de ces métaux dans les lagunes ivoiriennes. Cependant, aucune information n'est disponible pour prédire leur toxicité potentielle. Cette étude avait pour objectif de déterminer l'influence de la matière organique sur l'adsorption du plomb et du cadmium par les sédiments de la b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…Parmi les procédés de traitement des eaux polluées par les colorants organiques, l'adsorption s'avère être le plus efficace (Ertaş et al, 2010 ;Yao et Kouassi, 2015). Le charbon actif est l'un des adsorbants le plus utilisé à ce sujet (Sark et al, 2015).…”
Section: Introductionunclassified
“…Parmi les procédés de traitement des eaux polluées par les colorants organiques, l'adsorption s'avère être le plus efficace (Ertaş et al, 2010 ;Yao et Kouassi, 2015). Le charbon actif est l'un des adsorbants le plus utilisé à ce sujet (Sark et al, 2015).…”
Section: Introductionunclassified
“…In the Ebrié lagoon, the preferred site for Cd accumulation is sediment according to the high values of Rd obtained. This means that the portion of Cd that is soluble in water is very low, according to the observation of Yao and Kouassi (2015). This also explains the non-significant variation in Cd contents obtained in the water column, despite the fact that Cd was not detected in the sediments of several sites.…”
Section: Effect Of Physico-chemical Conditions On Tilapia Fish Contammentioning
confidence: 91%
“…However, determination of lead contamination level in aquatic system is important in order to control its pollution in the environment. Several studies have shown that tropical estuarine sediments were highly contaminated by Pb (Chakraborty et al, 2015;Kouassi et al, 2015;Yao and Kouassi, 2015;Chen et al, 2016;Botwe et al, 2017). However, these studies have not focused on seasonal accumulation of Pb in seaport sediments.…”
Section: Introductionmentioning
confidence: 99%